Estimation of seed yield and yield attributes by cumulative temperature in common bean (Phaseolus vulgaris) - KUMAR, A; OMAE, H (The Indian Journal of Agricultural Sciences, 2011)
The performance of common bean (Phaseolus vulgaris L.) cultivars was evaluated during three seasons (2003-05) under field conditions at Okinawa Subtropical Station, Ishigaki, Okinawa, Japan. Seed yield and yield-attributes data were collected to identify the important traits forming the yield and related with genotypic diversity in stability of productivity across the seasons. The cumulative temperatures from sowing to podding (mean across three seasons) in cultivars were within 1076.8–1553.5°C contributing to the estimation of seed yield per plant with a reasonable precision (R2=0.43). The number of pods/plant, which showed a highest correlation coefficient with seed yield was well predicted (R2=0.57) by multiple regression equations in which cumulative temperature from sowing to podding and duration from flowering to emergence were used as independent variables. The cultivars ‘Ishigaki 2’, ‘Haibushi’ and ‘Kurodane Kinugasa’ which gave the highest seed yield were the shortest in development and with the highest number of pods/plant. The results indicated that the early cultivars have smaller cumulative temperature from sowing to podding, thus shorter in development till podding and higher number of pods/plant and seed yield.